Molecular sieve confinement platinum-based catalyst and application thereof in catalysis of waste plastics

The molecular sieve limited-domain platinum-based catalyst Pt@Hie-TS-1 synthesized by hydrothermal method and synthesized with β-zeolite, solving the problem of low liquid yield in the catalytic decomposition of plastics in the prior art, and achieving high selective liquid alkane products and high catalytic effect, reducing the amount of platinum.

CN119318986APending Publication Date: 2025-01-17UNIV OF JINAN

Patent Information

Application Number
CN202411266791.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The existing molecular sieve catalysts have high reaction temperatures and low liquid yields and high gas yields, making it difficult to achieve the optimal catalytic effect.

Method used

The molecular sieve limited domain platinum-based catalyst Pt@Hie-TS-1 was synthesized by hydrothermal method. Through synergistic effects with β-zeolite, the liquid yield and selectivity of polyethylene plastics were improved, and the shape selectivity of Pt@Hie-TS-1 was used. and the pore shape selection effect, promoting hydrocracking of C5-C7 hydrocarbons.

Benefits of technology

A high selectivity liquid alkane product was achieved, and the liquid oil yield reached 93.5%, which reduced the amount of precious metal platinum, increased the contact area between the catalyst and the plastic, and increased the hydrocracking rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005037356530000011
    Figure HDA0005037356530000011
  • Figure HDA0005037356530000012
    Figure HDA0005037356530000012
  • Figure HDA0005037356530000013
    Figure HDA0005037356530000013
Patent Text Reader

Abstract

The invention discloses a molecular sieve confinement platinum-based catalyst and application thereof in catalysis of waste plastics, the Pt-coated Hie-TS-1 catalyst is prepared through hydrothermal synthesis, the catalyst has a hierarchical structure, the contact area between the catalyst and polyethylene plastics is increased, the hydrocracking rate is increased, the pore channel selectivity for polyolefin is achieved, and the molecular sieve confinement platinum-based catalyst can be used for catalyzing the polyethylene plastics. Catalytic products are distributed and diverted to narrow distribution, alkane and olefin intermediates are selectively filtered in Pt-Hie-TS-1 according to the length and the size, the shape selectivity of C5-C7 olefins is adjusted, the selectivity of C5-C9 hydrocarbons reaches 94.9%, and the use amount of Pt can be reduced to 0.4; the obtained product has the highest liquid oil content, the total amount of liquid oil can reach 93.5%, and the catalytic effect is the best.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of molecular sieves, and in particular relates to a molecular sieve confined platinum-based catalyst and application thereof in catalyzing waste plastics. Background Art

[0002] Plastics are widely used synthetic consumer products, and are also widely used in electronic products and household items. However, the large-scale application of plastics also produces a large amount of plastic waste, with about 400 million tons of plastic waste generated each year worldwide. The accumulation of waste plastics has caused serious environmental pollution, and microplastics have even entered the ecosystem through biological cycles. This continuous accumulation not only threatens biodiversity, but also undermines the sustainability of ecosystems and human health. Therefore, solving the challenge of plastic waste management is critical to achieving a more balanced and environmentally friendly future.

[0003] In addition to incineration, waste plastics can also be recycled by biodegradation, pyrolysis, hydrocracking and other methods. Among them, the recycling of plastics requires a catalyst to achieve a better recycling effect. The principle of plastic catalytic recycling is to convert waste plastics into high-value-added chemicals or fuels through the action of catalysts. Waste plastics can also be catalytically cracked to selectively obtain products with high added value.

[0004] In the prior art, molecular sieve catalysts are mostly used for catalytic decomposition of polyethylene, but the reaction temperature is usually higher than 400°C, and more low-carbon alkane gas will be produced. In order to obtain a saturated liquid fuel product with a higher yield, a molecular sieve-loaded noble metal-based catalyst is usually used. CN117225463A discloses a Pt / ZSM-5 supported catalyst for high-density polyethylene catalytic cracking reaction and its preparation method and application. The interaction between metal and molecular sieve carrier is used to regulate the acid site and electron density of the catalyst, and the regulation of the high-density polyethylene catalytic cracking reaction performance is achieved, so that the prepared catalyst can produce a higher liquid hydrocarbon yield under relatively mild conditions. The conversion rate of the Pt / ZSM-5 supported catalyst in the high-density polyethylene catalytic cracking reaction is greater than 70%, and the liquid hydrocarbon yield is about 50%, but because the liquid yield does not reach the maximum catalytic effect, the gas yield is still high, and the liquid yield has a large room for improvement.

[0005] Based on this, the present application proposes a molecular sieve confined platinum-based catalyst to solve the above problems, obtain a higher liquid yield, and obtain a highly selective liquid alkane product. Summary of the invention

[0006] This application proposes a molecular sieve confined platinum-based catalyst and its application in catalyzing waste plastics. The specific technical solution is as follows:

[0007] A molecular sieve confined platinum-based catalyst is prepared by a hydrothermal synthesis method. The catalyst can be used to catalyze low-density polyethylene.

[0008] Furthermore, the preparation method of the molecular sieve confined platinum-based catalyst is:

[0009] Step 1: Mix tetraethyl orthosilicate, tetrabutyl titanate, TPAOH and ethanol, stir in a water bath for 1-2 hours, then add isopropanol and stir for 3-4 hours to obtain solution A;

[0010] Step 2: Mix sodium hydroxide, water and 3-mercaptopropyltrimethoxysilane, stir to hydrolyze, add chloroplatinic acid, and stir to obtain solution B;

[0011] Step 3: Slowly add solution B into solution A, stir for 0.5-1.5h, then place in a reactor for crystallization, and then filter, wash, dry and calcine to obtain Pt@Hie-TS-1 catalyst.

[0012] In the step 1, the mass ratio of tetraethyl orthosilicate, tetrabutyl titanate, TPAOH, ethanol and isopropanol is 40-45:2.5-3:30-40:11-13:45-50;

[0013] In the step 2, the mass ratio of sodium hydroxide, water and 3-mercaptopropyltrimethoxysilane is 1:20:2;

[0014] The mass ratio of sodium hydroxide to tetrabutyl titanate is 1:25-27; the mass ratio of H2PtCl6 to tetrabutyl titanate is 1:1-1.3;

[0015] In the step 3, washing is performed with deionized water; drying is performed in an oven at a drying temperature of 80-100° C.; and calcination is performed in a muffle furnace at 500-550° C. for 2-3 hours.

[0016] The invention discloses an application of a molecular sieve confined platinum-based catalyst in catalyzing waste plastics. The molecular sieve confined platinum-based catalyst and beta zeolite can improve the liquid yield of polyethylene plastic waste and have high selectivity for C5-C9 hydrocarbons, especially having a higher yield and selectivity for C5-C7 hydrocarbons.

[0017] Technical principle

[0018] The synergistic effect of Pt@Hie-TS-1 and β-zeolite is beneficial to the hydrogenation of light olefins and enhances the cracking of high molecular intermediates. The main diffusion of C5-C7 olefins accelerates their interaction with Pt sites, thereby promoting the emergence of high selectivity for C5-C7 alkanes as final products. The shape selectivity of Pt@Hie-TS-1 is beneficial for olefin intermediates of specific sizes to meet with Pt sites, just like the "lock" model, while larger molecular intermediates are redirected on β-zeolite for secondary cracking in the intermittent reactor, which increases the yield of waste plastics hydrocracking to liquid oil. The more C the hydrocracking product contains, the easier it is to break the bond, and the less C the less likely it is to break the bond, so the yield in a certain interval will be very large, thus forming a normal distribution. Olefin intermediates are selectively filtered according to length and size in Pt@Hie-TS-1, utilizing the zeolite pore shape-selective effect. When the size and shape of the molecule match the pore, the molecule can be effectively adsorbed and diffuse into the pore; however, when the size of the molecule exceeds the pore size, the molecule may be excluded or unable to enter the pore, thereby ensuring the transport of C5-C7 hydrocarbons within the channel.

[0019] Technical Effects

[0020] The catalyst of the present application has a hierarchical structure, which increases the contact area between the catalyst and polyethylene plastic, improves the hydrocracking rate, has pore selectivity for polyolefins, and the product distribution shifts to narrow distribution alkanes. Olefin intermediates are selectively filtered according to length and size in Pt@Hie-TS-1, and the shape selectivity of C5-C7 olefins is adjusted, among which the selectivity of C5-C9 hydrocarbons reaches 94.9%, and the Pt dosage can be reduced to 0.4; the obtained product has the highest liquid oil content, the total amount of liquid oil can reach 93.5%, and the catalytic effect is the best. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 TEM and HRTEM images of Pt@Hie-TS-1 catalyst;

[0022] Figure 2 TEM and HRTEM images of Pt@TS-1 catalyst;

[0023] Figure 3 SEM image of Pt@Hie-TS-1;

[0024] Figure 4 EDS element mapping of Pt@Hie-TS-1;

[0025] Figure 5 Comparison of catalytic performance of different catalysts;

[0026] Figure 6The distribution diagram of catalytic products under different Pt@Hie TS-1 addition amounts while keeping β constant;

[0027] Figure 7 Distribution diagram of catalytic products at different reaction temperatures;

[0028] Figure 8 Distribution diagram of catalytic products at different reaction pressures. DETAILED DESCRIPTION

[0029] The implementation of the technical solution of the present invention and the beneficial effects thereof are described in detail below through specific embodiments, but they cannot be regarded as any limitation on the applicable scope of the present invention.

[0030] Example 1

[0031] A mixture containing 40.0 g of tetraethyl orthosilicate, 2.6 g of tetrabutyl titanate, 30.0 g of ethanol, and 46.7 g of TPAOH (25 wt%) was stirred for 1 hour. The solution was moved into a water bath at 70°C and stirred for 3 hours. 48 g of isopropanol was added and stirred for 1 hour to obtain 1 hour. At the same time, 0.1 g of NaOH, 2.0 g of water, and 0.2 g of 3-mercaptopropyltrimethoxysilane were mixed and stirred for 30 minutes for hydrolysis. Subsequently, 6.15 ml of H2PtCl6 (100 Mml) was added. -1 ), and continued stirring for 1 hour to obtain solution II. The second solution was slowly added to the first solution, and continued stirring for 30 minutes, and then transferred to a 170°C autoclave for crystallization for 24 hours. Finally, it was washed with deionized water and then dried in an oven at a drying temperature of 100°C; after drying, it was calcined in a muffle furnace at 550°C for 3 hours to obtain Pt@Hie-TS-1.

[0032] Figure 1 The Pt@Hie-TS-1 zeolite with layered self-pillared nanocrystal morphology is shown, showing that the Pt@HieTS-1 catalyst is composed of regular self-pillared zeolite crystals with an average size of about 180nm. HRTEM images show that Pt nanoparticles (dark spots) are dispersed in the Hie-TS-1 zeolite crystals. Figure 3 The SEM image of Pt@Hie-TS-1 also shows the hierarchical structure of the catalyst. Compared with traditional granular zeolite, the hierarchical structure increases the contact area between the catalyst and polyethylene plastic and improves the hydrocracking rate. Figure 5 The HAADF-STEM image of Pt@Hie-TS-1 shows that the catalyst surface is dense and uniform. The corresponding EDS element distribution map shows that Pt (yellow), Si (red) and Ti (blue) elements exist on the catalyst surface. At the same time, the Pt element mapping map also shows that Pt nanoparticles exist uniformly inside the zeolite catalyst.

[0033] Example 2

[0034] A mixture containing 40.0 g of tetraethyl orthosilicate, 2.6 g of tetrabutyl titanate, 30.0 g of ethanol, and 46.7 g of TPAOH (25 wt%) was stirred for 1 hour. The solution was moved into a water bath at 70°C and stirred for 3 hours. 48 g of isopropanol was added and stirred for 1 hour to obtain 1 hour. At the same time, 0.1 g of NaOH, 2.0 g of water, and 0.2 g of 3-mercaptopropyltrimethoxysilane were mixed and stirred for 30 minutes for hydrolysis. Crystallization was carried out in an autoclave at 170°C for 24 hours, and then filtered, washed, and dried. The solid product was then immersed in 100 Mml -1 The product was added to a H2PtCl6 solution, allowed to stand for 24 hours, filtered, washed with deionized water, and dried in an oven at 100°C. After drying, it was calcined at 550°C in a muffle furnace for 3 hours to obtain Pt@TS-1.

[0035] Figure 2 The Pt@TS-1 has a regular square block crystal structure, which is completely different from the structure of Example 1, which affects the difference in the catalytic plastic effect between the two.

[0036] Pt@Al2O3 and Pt@SiO2 are conventional molecular sieve supported synthesized in the art. Except for the different components, other operations are consistent with the condition parameters of Example 1.

[0037] The evaluation of the LDPE hydrocracking performance was carried out in a 50 mL autoclave reactor. Specifically, the catalyst was fully physically mixed with LDPE in the reactor and then sealed. The residual air in the reactor was purged with N2 three times. Hydrogen was then charged to the target pressure and the temperature was raised to the desired level to initiate the reaction, marking the start of the timing process. After the reaction was completed, the gaseous products were collected from the head space and analyzed using flame ionization detection gas chromatography (GC-FID) equipped with an SH-alumina BOND / Na2SO4 column. The mixture of liquid and solid was weighed. The liquid product was extracted with CH2Cl2 as the extractant, the liquid phase was separated by filtration, and GC analysis was performed using an MXT-1 column. Hexadecane was used as an internal standard to determine the product yield and selectivity at different carbon numbers. The residue was obtained after drying, and the gas yield was obtained based on the difference in mass balance.

[0038] Depend on Figure 5It can be seen that the product liquid oil content obtained by the β+Pt@Hie-TS-1 catalyst is the highest, with a yield of about 93% and the best catalytic effect; the liquid content of the cracking product catalyzed by the simple β catalyst or Pt@Hie-TS-1 is less, with a yield of 11%, indicating that the catalytic effect of the single catalyst is poorer than that of the β+Pt@Hie-TS-1 catalyst. This is because although the single β zeolite has B acid sites, it lacks metal sites and has poor hydrogenation ability for olefin intermediates. At the same time, the catalytic effect of the Pt@TS-1 catalyst is poor, with only a very small amount of liquid produced. This is because the single Pt@TS-1 lacks B acid sites and it is difficult to effectively break the CC bonds of long-chain polymers. The β+Pt / Al2O3 catalyst shows a liquid yield of about 68% under the same reaction conditions, which is mainly affected by the small surface area and metal dispersion. The Pt / β catalyst has poor activity and produces less liquid products because the strong interaction between the metal Pt and the β zeolite leads to severe carbon deposition on the B acid sites, thereby hindering the initial cracking. In addition, among the combinations of β-acid catalysts and various metal catalysts (β+Pt@TS-1, β+Pt / Al2O3, β+Pt / SiO2, etc.), β+Pt@Hie-TS-1 catalyst has the best catalytic effect.

[0039] At the same time, the catalytic products of the above different combinations are also different. The product distribution shifts to narrow distribution alkanes, among which the selectivity of C5-C9 hydrocarbons reaches 94.9%, which is much higher than the previous 50-60%. It may be due to the pore shape selectivity effect. This selectivity enables materials with pore structures to achieve selective adsorption and transfer of different molecules in processes such as adsorption, separation and catalysis. The pore shape selectivity of Pt@Hie-TS-1 zeolite enables short-chain olefin intermediates to have a faster diffusion rate in the zeolite pores. The main diffusion of C5-C7 olefin intermediates accelerates their interaction with Pt sites, thereby promoting the emergence of high selectivity for C5-C7 alkanes as final products. The shape selectivity of Pt@Hie-TS-1 is conducive to the encounter of olefin intermediates of specific sizes with Pt sites, just like the "lock-key" model, while larger molecular intermediates are redirected on β zeolite for secondary cracking until they are cracked into light olefins of suitable size. Olefin intermediates are selectively filtered in Pt@Hie-TS-1 based on length and size to ensure the transport of C5-C7 hydrocarbons within the channel, guaranteeing a narrow product distribution. Figure 7 It can be clearly seen that the matching zeolite beta and Pt@Hie-TS-1 are beneficial to the hydrogenation of light olefins and enhance the cracking of polymer intermediates. It is worth noting that due to the presence of confined metals in the Pt@Hie-TS-1 catalyst, Pt can be reduced to 0.4 without showing any significant decrease in conversion rate and product selectivity. This is conducive to reducing the use of precious metals.

[0040] Figure 7 It shows that as the reaction temperature increases, the proportion of liquid oil in the product increases, while when the temperature is higher than 270°C, the yield decreases relatively but not significantly, indicating that at temperatures above 270°C, the hydrogenation reaction is more affected by kinetics than thermodynamics. Therefore, the reaction temperature should not be too high or too low, and the appropriate reaction temperature is 250-270°C. Figure 8 It shows that within the reaction pressure range of 1 to 3 MPa, the liquid oil content in the waste plastic hydrocracking products is relatively high, basically maintained at above 92%. Under 1-2 MPa conditions, the total amount of synthesized liquid oil reaches 93.5%, indicating that the optimal pressure for waste plastic hydrocracking is 1-2 MPa.

Claims

1. A molecular sieve confined platinum-based catalyst, characterized in that: A molecular sieve confined platinum-based catalyst is prepared by a hydrothermal synthesis method. The molecular sieve confined platinum-based catalyst can be used to catalyze waste plastics. The molecular sieve confined platinum-based catalyst and beta zeolite can increase the liquid yield of polyethylene plastic waste.

2. A method for preparing a molecular sieve confined platinum-based catalyst as claimed in claim 1, characterized in that: The preparation method of the molecular sieve confined platinum-based catalyst is as follows: Step 1: Mix tetraethyl orthosilicate, tetrabutyl titanate, TPAOH and ethanol, stir in a water bath for 1-2 hours, then add isopropanol and stir for 3-4 hours to obtain solution A; Step 2: Mix sodium hydroxide, water and 3-mercaptopropyltrimethoxysilane, stir to hydrolyze, add chloroplatinic acid, and stir to obtain solution B; Step 3: Slowly add solution B into solution A, stir for 0.5-1.5h, then place in a reactor for crystallization, and then filter, wash, dry and calcine to obtain Pt@Hie-TS-1 catalyst.

3. A molecular sieve confined platinum-based catalyst as claimed in claim 2, characterized in that: In the step 1, the mass ratio of tetraethyl orthosilicate, tetrabutyl titanate, TPAOH, ethanol and isopropanol is 40-45:2.5-3:30-40:11-13:45-50.

4. A molecular sieve confined platinum-based catalyst as claimed in claim 2, characterized in that: In the step 2, the mass ratio of sodium hydroxide, water and 3-mercaptopropyltrimethoxysilane is 1:20:

2. The mass ratio of sodium hydroxide to tetrabutyl titanate is 1:25-27; the mass ratio of H2PtCl6 to tetrabutyl titanate is 1:1-1.

3.

5. A molecular sieve confined platinum-based catalyst as claimed in claim 2, characterized in that: In the step 3, washing is performed with deionized water; drying is performed in an oven at a temperature of 80-100° C.; and calcination is performed in a muffle furnace at a temperature of 500-550° C. for 2-3 hours.

6. Use of a molecular sieve confined platinum-based catalyst as claimed in any one of claims 1 to 5 in catalyzing waste plastics, characterized in that: The waste plastic is low-density polyethylene, and the molecular sieve confined platinum-based catalyst has a higher yield and selectivity for C5-C7 hydrocarbons.

Citation Information

Patent Citations

  • Pt / ZSM-5 supported catalyst for catalytic cracking reaction of high-density polyethylene as well as preparation method and application of Pt / ZSM-5 supported catalyst

    CN117225463A

Cited By

  • EMT / FAU eutectic molecular sieve catalyst and preparation method and application thereof

    CN120325317A

  • Mesomicroporous core-shell molecular sieve series beta zeolite catalyst and preparation method and application thereof

    CN120790222A

  • Mesoporous core-shell molecular sieve tandem β-zeolite catalysts, their preparation methods and applications

    CN120790222B

  • EMT / TS-1 mixed crystal molecular sieve, preparation method thereof and application of EMT / TS-1 mixed crystal molecular sieve in polyethylene waste hydrocracking

    CN120838472A